The impact of management, family, and institution on the auditor's going concern opinion issuance decision - Osman, Mohammad Noor Hisham; Abdul Latiff, Ahmed Razman; Mat Daud, Zaidi; Muhamad Sori, Zulkarnain (Faculty of Economics and Management, Universiti Putra Malaysia, 2018)
Incidents where external auditors do not issue a going concern audit opinion (GC opinion) to companies having severe financial problems have been reported globally. This issue motivated this study – (i) to investigate the effect of selected auditor characteristics in terms of specialization, tenure, and fee on GC opinion issuance and (ii) to examine the moderating effect of management’s, family’s, and institution’s influence on the relationship between auditor characteristics and GC opinion issuance. The study involves 644 Malaysian financially distressed listed companies in the period 2006 to 2012. The results of a panel logistic regression analysis show that auditor characteristics have no relationship with GC opinion issuance. Influential management - measured as the level of their ownership - can dampen the positive relationship between auditor specialization and auditor tenure with GC opinion issuance. The presence of an influential family, on the other hand, can strengthen the positive relationship between auditor tenure and GC opinion. No evidence about an influential institution’s impact on the GC opinion process could be found. In conclusion, while auditor characteristics do not affect the possibility of a GC opinion issuance, pressure imposed by influential management and family on the auditor during the audit opinion decision process does have an impact.